Gender Representation in Perpustakaan Intan - Riskia Setiarini; Supiastutik Supiastutik; Dina Dyah Kusumayanti; Hadi Sampurna; Erna Cahyawati (Pioneer: Journal of Language and Literature, 2021)
There is little research on gender-related children's picture books in Indonesia. In this article, we discuss the disclosure of gender representation in a picture book entitled Perpustakaan Intan. The high number appearances of women, the actions pinned on women, and the clothes displayed in both text and images are materials for visualizing women and men. Previous studies have revealed that men dominate the number of appearances in books. However, this book displays women more often than men. On the one hand, this raises the question of whether this means women are in power, and on the other hand, men are portrayed as powerless. Utilizing the multimodality approach, the results show that although women appear more in the narrative, women are still represented as less powerful.